Gambaran Kualitas Partikel Debu Respirable Pada Karyawan Pengrajin Perahu UD. Aira Fiberglass Di Dusun Kalauli Negeri Kaitetu Kecamatan Leihitu Kabupaten Maluku Tengah - Kornelis Urbanus Rumselly; Zulfikar Peluw (Jurnal Medika Nusantara, 2025)
According to WHO, the size of dust particles can range from 0.1-5 or 10 microns, while the Indonesian Ministry of Health suggests that the size of dangerous dust is in the range of 0.1-10 microns. Based on the Republic of Indonesia Minister of Health Regulation No. 13 of 2011 concerning the threshold value for chemical factors in places where the maximum dust content in the workplace is 3mg/Nm3 (WHO 2018). This research aims to determine the dust levels at UD. Aira Fiberglass in Kalauli Hamlet, Kaitetu District, Leihitu District, Central Maluku Regency. The type of research used is descriptive research supported by laboratory examinations to see the results of measuring exposure to Respirable dust in UD Furniture. Aira Fiberglas, Leihitu District, Central Maluku Regency. Based on the results of research on dust measurements, it can be concluded that the dust on UD furniture. Aira Fiberglass examined at the Maluku Occupational Safety and Health Development Center UPTD, 70% met the requirements and 30% did not meet the requirements. Based on the results of research on dust measurements, it can be concluded that there are employees who have dust levels that exceed the Threshold Limit Value (NAB). ) 3. For this reason, efforts are needed to improve the work environment, especially ventilation and education on PPE (masks) for employees.